Taxonomy and phylogeny of Cercospora spp. from Northern Thailand - Nguanhom, Jeerapa; Cheewangkoon, Ratchadawan; Groenewald, Johannes Z.; Braun, Uwe; To-Anun, Chaiwat; Crous, Pedro W. (Phytotaxa, 2015)
The genus Cercospora represents a group of important plant pathogenic fungi with a wide geographic distribution, being commonly associated with leaf spots on a broad range of plant hosts. The goal of the present study was to conduct a morphological and molecular phylogenetic analysis of the Cercospora spp. occurring on various plants growing in Northern Thailand, an area with a tropical savannah climate, and a rich diversity of vascular plants. Sixty Cercospora isolates were collected from 29 host species (representing 16 plant families). Partial nucleotide sequence data for two gene loci (ITS and cmdA), were generated for all isolates. Results from this study indicate that members of the genus Cercospora vary regarding host specificity, with some taxa having wide host ranges, and others being host-specific. Based on cultural, morphological and phylogenetic data, four new species of Cercospora could be identified: C. glycinicola (from Glycine max), C. cyperacearum and C. cyperina (from Cyperus alternifolius), and C. musigena (from Musa sp.). The most common Cercospora sp. found in Northern Thailand was C. cf. malloti, which occurred on a wide host range. Several collections could not be resolved to species level due to the lack of reference cultures and DNA data for morphologically similar species. Further collections from other countries are needed to help resolve the taxonomy of some species complexes occurring on various plant hosts in Thailand.